(3eWdY GdahGFO heLeY GdaQGFOs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s ((3eMehO CHhGdehGgH GdTgjQ HCHj Oajg s)
(3ChdgG (B:s
(3MeOkG ddg eDJj GdMceI ef TGA ef Ndbg aEf gPg GdUfGYI GdCOHjI SfjI GdeWGdY s
(3BNQgG (B:s
(3hJMa JZfj GdeJCed ef fXje hfKjQ, Ydi MSH eG jSYg UOQg hjSgd CeQg s
(3GfXQ GdLRA GdChd Qbe (B769 (3COHs
(3eLehYI ef eNJGQ GdfXe hGdfKQ eQJHI Ydi GdeYGfjs
(3HOGNdgG ebOGQ hQbI Hbde aGQSjs
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdCOHs